Piercing the left lung with a pacemaker lead, an uncommon complication - Hassan, A.A. (2004)
Although percutaneous insertion of pacemaker leads is a simple and safe method, it remains a procedure with a relatively high complication rate. We describe an uncommon and avoidable complication of this technique: piercing the lung with a pacemaker lead in an obese patient after direct puncture of the subclavian vein.